2014
DOI: 10.1302/0301-620x.96b12.34468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Instability Severity Index Score and the Western Ontario Shoulder Instability Index as predictors of failure following arthroscopic Bankart repair

Abstract: In this study we evaluated whether the Instability Severity Index Score (ISIS) and the Western Ontario Shoulder Instability Index (WOSI) could detect those patients at risk of failure following arthroscopic Bankart repair. Between April 2008 and June 2010, the ISIS and WOSI were recorded pre-operatively in 110 patients (87 male, 79%) with a mean age of 25.1 years (16 to 61) who underwent this procedure for recurrent anterior glenohumeral instability. A telephone interview was performed two-years post-operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 23 publications
2
29
0
4
Order By: Relevance
“…Another potential study weakness is the lack of inter-rater and intrarater reliability of the score, specifically for the radiographic portion. We agree with Bouliane et al 8 that improving the radiographic component of the ISI Score would serve to strengthen the score and further enhance its clinical utility. The use of 2-or 3-dimensional imaging provides a more accurate representation of bony lesions and is part of our routine imaging studies in patients with unstable shoulders.…”
Section: Validity Of Isi Scoresupporting
confidence: 89%
See 2 more Smart Citations
“…Another potential study weakness is the lack of inter-rater and intrarater reliability of the score, specifically for the radiographic portion. We agree with Bouliane et al 8 that improving the radiographic component of the ISI Score would serve to strengthen the score and further enhance its clinical utility. The use of 2-or 3-dimensional imaging provides a more accurate representation of bony lesions and is part of our routine imaging studies in patients with unstable shoulders.…”
Section: Validity Of Isi Scoresupporting
confidence: 89%
“…5 The Instability Severity Index (ISI) Score is a useful tool that has already changed the approach to the treatment of post-traumatic glenohumeral instability in Europe and Canada. [6][7][8][9] At the moment, this scoring system remains poorly known and used in the United States, but it is our opinion that such a tool deserves to be spread among shoulder surgeons. 10 important question for both surgeons and patients.…”
Section: See Related Article On Page 361mentioning
confidence: 99%
See 1 more Smart Citation
“…Thomazeau et al 4 similarly suggested that an ISIS 4 is ideal for arthroscopic Bankart repair. In contrast, Bouliane et al 5 concluded that ISIS was incapable of predicting recurrent instability in their cohort of 110 patients at 2 years after arthroscopic Bankart repair.…”
Section: See Commentary On Page 68mentioning
confidence: 90%
“…However, it is not only just the presence of glenohumeral bone loss, but also the interplay between the glenoid and humeral lesions, as suggested by the glenoid track concept, that contribute to recurrent instability. 5,21 According to the glenoid track concept, which has been verified biomechanically and clinically, 19,28 a Hill-Sachs lesion may be characterized as "on-track" or "off-track." 29 An off-track lesion is one with bipolar bone loss that engages between the Hill-Sachs lesion and glenoid rim and increases the risk of recurrent stability if bone loss is not addressed.…”
Section: Discussionmentioning
confidence: 99%